2011
DOI: 10.1177/1742395311411591
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of families of a child with a nut allergy

Abstract: In many ways, nut allergy may be considered a form of disability, because it imposes social barriers on participating fully in society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 28 publications
6
67
0
Order By: Relevance
“…As with the existing literature, intrusion of a chronic illness as found in the present study affected the relationship between the food provider and the patient (11)(12)(13)(14)(15)(16)(17)(18) . This distress was related to people's level of familiarity with attending guests and aspects of the interpersonal dynamics of the relationships.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As with the existing literature, intrusion of a chronic illness as found in the present study affected the relationship between the food provider and the patient (11)(12)(13)(14)(15)(16)(17)(18) . This distress was related to people's level of familiarity with attending guests and aspects of the interpersonal dynamics of the relationships.…”
Section: Discussionsupporting
confidence: 72%
“…Within the home, interpersonal conflict within the family may arise as a result of differing views around food preparation and provision , where both activities are laden with challenging emotional content for the family . Similar emotional and lifestyle disruption around therapeutic diets has been reported in families living with epilepsy , food allergy childhood constipation , colon cancer , prostate cancer , autism , hypercholesterolaemia and coeliac disease . This breadth of evidence across a range of conditions reflects the importance of the issue.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The second contributing factor to risk-taking was due to their children's desire to take part in social experiences at school without feeling stigmatized for having a food allergy. While parents' desire to ease the social isolation and stigma faced by their food allergic children has been documented elsewhere, 28 we believe that this is exacerbated by the want of new immigrants to find acceptance and integration into the society of their new home putting the parents of food allergic parents in a double jeopardy situation.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study of families of a child with a peanut allergy, researchers found that parents report being treated as “faddy” or “neurotic” (Pitchforth et al, 2011). In one study that distinguished those with food allergies and those with food intolerances, Nettleton et al (2010) found that respondents without medically-defined symptoms realize their condition as more of a social problem that those with a medically-conferred diagnosis of allergy.…”
Section: Discussionmentioning
confidence: 99%